Vectorial form of Ekeland variational principle with applications to vector equilibrium problems. (3rd March 2020) - Al-Homidan, Suliman; Ansari, Qamrul Hasan; Kassay, Gabor
ABSTRACT: We first derive an Ekeland type variational principle for vector-valued bifunctions without assuming triangular inequality for bifunctions. Then, by using such variational principle, we derive some existence results for solutions of vector equilibrium problems and vector quasi-equilibrium problems.